PENCEGAHAN DEMAM BERDARAH PADA MASYARAKAT DUSUN MONGKRONG GUNUNG KIDUL - Rahmawan, Alfian; Ma'ruf, Farid (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2020)
DBD is an infectious disease by the Dengue virus, which is transmitted through the bite of Aedes aegypti mosquitoes. This disease's characteristics include sudden high fever accompanied by bleeding manifestations and the tendency to cause shock that can cause death. Until now, there is no cure for dengue fever or a vaccine. So the only way to prevent this disease is to break the chain of transmission. The main factor of dengue fever in Indonesia is the Aedes aegypti mosquito. Another way to avoid dengue fever is the correct 3M plus method, namely 1. Close, cover all places that can hold water, both inside and outside the house. 2. Drain, drain water reservoirs such as bathtubs, aquariums, and flower vases two times a week. The mosquito metamorphosis cycle, from egg to adult mosquito, lasts 8-10 days. 3. Bury. Bury all objects that can hold water, such as used cans or plastic containers. However, in the 3M movement, which has been renewed to 3M plus, this third M is no longer recommended because it can cause soil pollution